OPTIMIZATION OF TREATMENT FOR BRONCHIOLITIS IN CHILDREN WITH ALLERGIES - Shokirova Shoxsanam Botirovna; Ibragimova Marina Fedorovna (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Introduction: Bronchiolitis remains one of the most common causes of lower respiratory tract disease in young children. The presence of an allergic background contributes to a more severe and protracted course of the disease due to bronchial hyperreactivity, a pronounced inflammatory response, and a tendency toward bronchoconstriction. Bronchiolitis associated with allergies is characterized by frequent episodes of expiratory dyspnea, a prolonged cough, and a decreased effectiveness of standard therapy. In this regard, optimizing treatment strategies based on the patient’s allergic status is essential. A comprehensive approach, including basic bronchiolitis therapy in combination with Bronchomunal and individualized risk factor management, facilitates faster symptom relief. Optimizing bronchiolitis treatment in children with a history of allergies improves the clinical course of the disease, shortens hospitalization, and reduces the risk of recurrent bronchoobstruction in the future.